Evaluation of large structural grillages subjected to ice loads in experimental and numerical analysis. (September 2018) - Kim, Hyunmin; Daley, Claude; Kim, Hyunwook
Abstract: Laboratory-grown cone-shaped ice specimens (1 m diameter) were utilized to load large structural grillages into a plastic response domain. The scantlings of the grillages were typical of a transversely framed mid-body ice belt arrangement of a 10, 000 ton Ice Class PC6 vessel. The maximum loads reached levels well beyond the elastic limit of the material and any acceptable plastic design point. The tests allowed for an evaluation of highly non-linear structural behavior and overload capacity considering the simultaneous failure of ice. Two separate large structural grillage tests were carried out with ice specimens loaded at a quasi-static loading rate (0.5 mm/s). The first set of tests were performed in two loading steps at identical loading positions at the mid-span of the central stiffener. The second set of tests were carried out in three loading steps at different loading positions along the span of the central stiffener of the grillage as a sequence of right-off, center, and left-off center. The experiments led to unique insight into the overload response and load carrying capacity of a large structural grillage as well as the effect of prior plastic damage on the structural behavior. Load-deflection curves and deformed shapes measured by MicroScribe ® were compared with the results of nonlinear finite element (FE) analysis. The FE analysis results show a strong agreement with the physical experiments, which confirms that the nonlinear FE analysis is a suitable tool for the analysis of ice-strengthened ship structures subjected to extreme ice loading. Highlights: Lab-grown ice specimen were utilized to load the grillages into a plastic response domain. Maximum loads reached levels beyond the elastic limit of the material. Highly non-linear structural behavior and overload capacity considering ice failure were evaluated. Effect of prior plastic damage on the structure was investigated and discussed. Results of FE analysis showed a good agreement compared with the physical experimental results.